(untitled) (Global Journal of Science Frontier Research, 2018)
A study was conducted to evaluate the effects of the inclusion of graded levels of Morning glory (Ipomoea asarifolia) leaf meal in the diets of growing rabbits on growth performance, nutrients retention, and carcass characteristics. Four experimental diets were formulated, with inclusion levels of 0, 5, 10 and 15 g/kg of Ipomoea asarifolia leaf meals as T 1 , T 2 , T 3 and T 4 respectively. Forty male rabbits used for the experiment were allotted to four treatments groups (1, 2, 3, and 4) with two rabbits per replicate in a completely randomized design. The rabbits were fed with the respective diets for 56 days. Parameters such as fed intake, weight gain, feed conversion ratio (FCR) and mortality rate where monitored. The data generated where subjected to analysis of variance (ANOVA). Where significant difference (P0.05).